2011
DOI: 10.1002/eji.201040760
|View full text |Cite
|
Sign up to set email alerts
|

Ly6C supports preferential homing of central memory CD8+ T cells into lymph nodes

Abstract: Ly6C is a murine cell-surface antigen expressed by plasma cells, subsets of myeloid cells and many T cells, including memory T cells. We previously documented that Ly6C crosslinking induces LFA-1 clustering on naïve CD8 1 T cells. Here, we show that in vitro and in vivo differentiation of naïve CD8 1 T cells into central (Tcm) but not effector (Tem) memory T cells enhances Ly6C expression, and its crosslinking induces strong LFA-1 clustering on Tcm. Blocking Ly6C function inhibits in vivo Tcm homing to LNs as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 45 publications
3
56
0
1
Order By: Relevance
“…Our data demonstrated that not only were all of these molecules more significantly upregulated but also that Ly6C, another TCM cellular marker implicated for preferential homing to the lymph nodes (19,28), was also highly expressed in Ad26 and Ad35 elicited Gagspecific CD8 ϩ T cells throughout the course of vaccination in mice compared to Ad5. Similar results were obtained by Yang et al in a study utilizing an Ad5-Ova system, with low expression of CD62L, CD127, and Ly6C in Ova-specific CD8 ϩ T cells 30 days postimmunization (29).…”
Section: Length Of Antigen Rest Between Priming and Boosting Impacts mentioning
confidence: 69%
“…Our data demonstrated that not only were all of these molecules more significantly upregulated but also that Ly6C, another TCM cellular marker implicated for preferential homing to the lymph nodes (19,28), was also highly expressed in Ad26 and Ad35 elicited Gagspecific CD8 ϩ T cells throughout the course of vaccination in mice compared to Ad5. Similar results were obtained by Yang et al in a study utilizing an Ad5-Ova system, with low expression of CD62L, CD127, and Ly6C in Ova-specific CD8 ϩ T cells 30 days postimmunization (29).…”
Section: Length Of Antigen Rest Between Priming and Boosting Impacts mentioning
confidence: 69%
“…In these studies, we took advantage of the cell surface antigen Ly6C, which is differentially expressed in classical and nonclassical peripheral blood monocytes, natural killer (NK) cells, and subsets of activated lymphocytes (63)(64)(65)(66). Importantly, previous studies have reported that Ly6C is not expressed by CNS-resident microglia (67).…”
Section: Resultsmentioning
confidence: 99%
“…C T cells, 111 and Ly6G ligation coordinates the recruitment of neutrophils in vivo, 112 suggesting that expression of Ly6C and Ly6G by IgA C PC might regulate their positioning and function. Importantly, expression of TNFa and iNOS in B lineage cells was shown to be critical for the maintenance of IgA levels as well as intestinal immune homeostasis at steady-state and after immune challenge with a gut-tropic pathogen, 1 suggesting a functional synergy of these 2 innate immune mediators for the regulation of intestinal PC functions.…”
Section: Ly6gmentioning
confidence: 99%